Influence of psychosocial factors on mathematics performance among Malaysian primary school students: a case study - Zhao, Y.; C. Hassan, Norlizah (2025)
Almost everything a person does involves mathematics, especially in this day and age of science and technology. Therefore, the aim of the study is to investigates the influence of psychosocial factors (self-efficacy, motivation and parental support) on mathematics performance of primary school